2013
DOI: 10.1136/sextrans-2013-051250
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing sources of HIV transmission from the distribution of newly acquired HIV infections: why is it important for HIV prevention planning?

Abstract: Impact of HIV prevention strategies may vary depending on whether they are directed by the long-term transmission source or by the distribution of new HIV infections. Caution is required when interpreting the 'source of HIV infections' to avoid misusing the distribution of new HIV infections in HIV prevention planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 21 publications
0
46
0
Order By: Relevance
“…It also captures the influence of FSW cross-border migration in a setting where the majority of FSW are not local nationals. The combination of good data and dynamical modelling has allowed a better appreciation of the contribution of sex work to overall HIV transmission than when relying on classical methods to estimate PAF [33][35].…”
Section: Discussionmentioning
confidence: 99%
“…It also captures the influence of FSW cross-border migration in a setting where the majority of FSW are not local nationals. The combination of good data and dynamical modelling has allowed a better appreciation of the contribution of sex work to overall HIV transmission than when relying on classical methods to estimate PAF [33][35].…”
Section: Discussionmentioning
confidence: 99%
“…With a national HIV prevalence of 3.7% in 2012 15 , the lessons learned from an in-depth review and comprehensive analysis of the past national response in Côte d'Ivoire would improve the evidence base for existing and future health policies. Further, recent studies have also shown the importance of understanding which subgroups of susceptible individuals are more likely to acquire new infections (i.e., the source of HIV acquisitions) and which groups of HIV positive individuals are more likely to transmit infections (i.e., the source of HIV transmissions) in the long-term using transmission dynamic models 16-18 . The source of HIV transmission, also called the transmission Population Attributable Fraction (PAF) 19 , incorporates not only information on infections from index cases to their partners but also from such secondary infected partners to their partners (i.e., chains of transmission).…”
Section: Introductionmentioning
confidence: 99%
“…The transmission PAF metric is more useful than the source of acquisitions to identify epidemic drivers - defined as the group with a risk factor that accounts for most of HIV transmission and for which transmission could be most efficiently prevented if it was blocked. As such, dynamic models of HIV transmission, such has the one used in this study, provide more useful information to inform HIV prevention programs than static model such as the Modes of Transmission metric 16,17,20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Malaria can be characterized by acquired immunity or, like HIV, a long asymptomatic and infectious period, particularly in the case of Plasmodium vivax [20]. In HIV, these circumstances have led to distributions of reported cases that often do not reflect the relative contribution of different subpopulations to transmission or the current epidemiological situation [21]. …”
Section: Introductionmentioning
confidence: 99%